EVALUATION OF THE KNOWLEDGE OF PHYSICIANS AND RESIDENT GYNECOLOGISTS AND OBSTETRICIANS ON SHOULDER DYSTOCIA (CIPEEX, 2025)
Shoulder dystocia (SD) is an obstetric emergency and can bring serious complications for both the mother and the newborn, and it is extremely important that the physician and their team are prepared to recognize and treat this situation in the best possible way. In this context, practical training on the topic, such as that offered by Advanced Life Support in Obstetrics (ALSO), is essential. Objective: To evaluate the knowledge of specialized physicians and obstetrics residents on the conduct and management of shoulder dystocia. Method: This is a cross-sectional, descriptive study, conducted in maternity hospitals and hospitals in Anápolis and Goiânia. The population included specialized physicians and residents working in the obstetrics area. Data were collected through an authorial questionnaire and tabulated in an Excel spreadsheet. For subgroup analysis, the Chi-square and Fisher's tests were used. Results: 38 questionnaires were collected, 19 from physicians and 19 from residents. Of these participants, 63% had already undergone some practical training in SD, but only 39% had participated in any ALSO course. Low percentages of knowledge were identified in the mnemonic (34%), in part 2 (57%), and in the second section of part 3 (52%) of the questionnaire. In subgroup analysis, both residents and those who had training in SD showed greater knowledge of the maneuvers. Conclusion: The participants' knowledge regarding SD maneuvers was lower than expected, being higher in the resident population. Furthermore, a significant impact of SD training on better performance in the questionnaire was observed.
Keywords: Shoulder dystocia; Health Professionals; Simulation Training